A Substrate Integrated Waveguide Slotted Antenna - V. G. Koshkid’ko; Ya. O. Galtsov; D. A. Portnykh (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. Slotted waveguide antenna arrays are widely used across centimeter- and millimeter-wavelength ranges due to numerous advantages, including their good directional properties, compact dimensions, flat shape, convenience of power supply, and high efficiency. At the same time, the current trend toward miniaturization of electronic devices and their integration requires new solutions, such as the development of devices based on wave-guides integrated into the substrate (Substrate Integrated Waveguide – SIW).Aim. To simulate a SIW-based slotted antenna with characteristics similar to those of a conventional antenna array based on a hollow metal waveguide.Materials and methods. The Ansys HFSS software was used to simulate the structure under study and to carry out electro-magnetic modeling and analysis of its directional properties. The energy method was used to determine the coordinates of longitudinal slots on the wide wall of the SIW waveguide. Macros were developed in the Visual Basic Scripting Edition language to automate routine operations for creating and deleting objects of the same type when constructing a model. The Arlon AD300C microwave material was used to manufacture a printed version of the SIW waveguide.Results. The process of developing a SIW slotted antenna was carried out in the following stages: construction of a reference model based on a hollow metal waveguide followed by creating a transition model based on a waveguide completely filled with a dielectric and the final SIW-based model. At each stage, the radiation pattern was monitored to obtain the directional properties of the SIW slotted antenna with characteristics identical to those of an antenna based on the reference hollow metal waveguide.Conclusion. A SIW slotted antenna with the required characteristics was simulated and tested in the Ansys HFSS environment. Such an antenna employs one of the main advantages of the SIW technology, i.e., the possibility of integrating all components on a single substrate, including antenna arrays, passive components, and active elements. This approach provides the basis for reducing the size of microwave devices and their miniaturization.